العنف المدرسي وعلاقته بأساليب المعاملة الوالدية لدى عينة من تلاميذ سنة اولى ثانوية العربي بن ذهيبة دراسة ميدانية ببلدية قلتة سيدى سعد الأغواط - سعيدي وفاء; عثماني فاطمة; النوعي بدرية (My University, 2022)
Our study aims to find out the relationship between school violence and parental treatment methods among first-year high school students, as well as to identify pupils who practice and who are exposed to it, as well as to reveal the differences between males and females in school violence. Hypotheses: - There is a statistically significant relationship between school violence and parental treatment methods. - There is a relationship between violent adolescents and parental treatment methods. - There is a relationship between adolescents engaging in violence and parental treatment - There are differences between males and females in school violence. Curriculum: We used analytical descriptive hybrids. Sample: The study was applied to 49 students at Al Arabi High School, bin Da'iba, Saida Saad al-Aguat Tool: The School Violence Questionnaire and the Parental Treatment Methods Questionnaire were applied, with the results resulting in no relationship between school violence and parental treatment methods, as well as no relationship between violent adolescents and school violence. School violence - parental treatment methods